2014
DOI: 10.1097/pec.0000000000000088
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Sinus Thrombosis in a 6-Year-Old Boy After a Minor Head Injury

Abstract: Posttraumatic cerebral sinus thrombosis is an uncommon disease in children that is rarely seen in the setting of a closed head injury. We report a 6-year-old boy who developed cerebral sinus thrombosis after an apparent minor head injury. The clinical presentation, neuroimaging findings, and treatment strategies are discussed. Serial neurological evaluation and close observation are important, and the decision for anticoagulation should be carefully considered with hematological consultants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…CVT has been associated with various etiologies including hypercoagulable states, head trauma, dehydration, oral contraceptives use, neoplastic invasion of a venous sinus, vasculitis, intracranial and systemic infections, congenital heart disease, anemia, pregnancy, and puerperium. [ 4 ] Oral contraceptive use is the only known risk factor in our patient. In addition to the absence of risk factors such as trauma, systemic or intracranial infection, dehydration, and vasculitis, the extensive laboratory evaluation for prothrombotic conditions showed normal findings.…”
Section: Discussionmentioning
confidence: 97%
“…CVT has been associated with various etiologies including hypercoagulable states, head trauma, dehydration, oral contraceptives use, neoplastic invasion of a venous sinus, vasculitis, intracranial and systemic infections, congenital heart disease, anemia, pregnancy, and puerperium. [ 4 ] Oral contraceptive use is the only known risk factor in our patient. In addition to the absence of risk factors such as trauma, systemic or intracranial infection, dehydration, and vasculitis, the extensive laboratory evaluation for prothrombotic conditions showed normal findings.…”
Section: Discussionmentioning
confidence: 97%
“…When there is adequate collateral venous circulation, or thrombosis occurs in a nondominant sinus, the patient may even be asymptomatic, which requires an even higher index of suspicion. 31 Historically, therefore, it has often been the presence of a skull fracture close to a venous sinus or an adjacent epidural hematoma that prompts workup for cerebral venous sinus pathology. In our series, this proximity of the fracture to a venous sinus was the most common reason that venous imaging was performed.…”
Section: Discussionmentioning
confidence: 99%
“…In our series, this proximity of the fracture to a venous sinus was the most common reason that venous imaging was performed. Although traumatic CVST has been found in the absence of a fracture, 31,51,52,56,62 various authors have identified a skull fracture overlying a dural venous sinus as an independent risk factor for sinus thrombosis. 11,31,42,45,56 Delgado Almandoz et al 11 found that among 159 pediatric and adult patients who presented to the emergency department with skull fractures, 57 patients (36%) had positive findings on CTV; all cases of thrombosis occurred in patients whose fracture extended to a dural venous sinus or the jugular bulb (which was the case in 140 of 159 patients).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several studies about CVST following a closed head injury in pediatrics ( Table 1 ). Twenty-three patients in 11 studies have been reported 8 9 13 16 17 20 22 23 25 26) . The frequently involved locations were the sigmoid sinus (69.6%) and the transverse sinus (52.2%).…”
Section: Discussionmentioning
confidence: 99%